2017
DOI: 10.1093/geronb/gbx115
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Comparison of Quantifications of Intraindividual Variability in Response Times: A Measurement Burst Approach

Abstract: RTI reflects a novel dimension of performance that is a robust and theoretically informative predictor of BP and WP variation in cognitive function. Among the plenitude of RTI quantifications, not all are interchangeable, nor of comparable predictive utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Thus, the RTI metric is in T-score units, with a single point on this scale reflecting 1/10 of an SD. The residualized ISD has numerous advantages over alternative quantifications; beyond being one of the most oft-used indicators of RTI, it also statistically controls for potential confounds including learning, practice effects, and individual differences in average RT (32,42). Further, previous research has shown that the residual ISD from a choice RT task exhibits adequate reliability and predictive validity with as few as 20 trials (25) and is a valid index across adulthood and older age (43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the RTI metric is in T-score units, with a single point on this scale reflecting 1/10 of an SD. The residualized ISD has numerous advantages over alternative quantifications; beyond being one of the most oft-used indicators of RTI, it also statistically controls for potential confounds including learning, practice effects, and individual differences in average RT (32,42). Further, previous research has shown that the residual ISD from a choice RT task exhibits adequate reliability and predictive validity with as few as 20 trials (25) and is a valid index across adulthood and older age (43).…”
Section: Methodsmentioning
confidence: 99%
“…Although correlated with standardized measures of neuropsychological status and cognitive ability, RTI shows unique sensitivity and clinical utility for predicting cognitive decline, cognitive impairment, and mortality (24). As such, it is potentially more sensitive for detecting subtle variations in processing efficiency, attributable to durable gradations in cognitive status and central nervous system integrity, as well as more transient fluctuations attributable to contextual influences such as daily stress processes (3032).…”
mentioning
confidence: 99%
“…The simplest of these is the intra-individual standard deviation (iSD), which is calculated as the standard deviation across standardized scores of different tasks for a single individual. This measure can be problematic when there are significant systematic group differences in average level of performance, as greater means tend to be associated with bigger variance ( Hale et al, 1988 ; Stawski et al, 2017 ). This can represent a serious confound in the case of comparison of performance between age-groups.…”
Section: Methodsmentioning
confidence: 99%
“…Third, while prior TestMyBrain.org sample studies have been replicated compared to traditionally collected and nationally representative US samples (Germine et al, 2011;Hartshorne and Germine, 2015), further validation work is recommended. Finally, our very brief measures of simple and choice RT were sufficient to produce reliable measures of psychomotor response speed, but did not allow us to employ more sophisticated model fitting techniques to trial-by-trial data that have been used in other studies of RT variability, such as estimation of multiple components of variability using an ex-Gaussian distribution (see McAuley et al, 2006;Matzke and Wagenmakers, 2009) or estimation of variability over longer time intervals, such as in a measurement burst design (Stawski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on variability in RTs within a task, rather than variability across trials within the same session (dispersion) or variability in scores at different timepoints (e.g., longitudinal variability, measurement burst designs, or ecological momentary assessment). While the latter forms of variability are potentially important and informative (e.g., Bielak et al, 2010;Stawski et al, 2019), they are related to fluctuations along longer time scales (hours, days, years) rather than the moment-to-moment variability we focus on for the purposes of this study. Future work might clarify whether within task RT variability that we examined here produces similar findings to measures of variability examined along longer time scales for choice and simple RT data (e.g., in ecological momentary assessment designs).…”
Section: Introductionmentioning
confidence: 99%